Evaluation of the Effectiveness of Occupationnal Safety and Health Management System in Railway Operations: Literatur Review - Naufal, Ahmad Fitra; Ramadhani, Dwi Ajeng; Maulana, Alfian; Hasibuan, Abdurrozzaq (Universitas Ibn Khaldun, 2025)
An effective Occupational safety and health management system is expected to create a safe and healthy working environment for all workers. In the context of railway operations, this system covers various aspects, ranging from safety training, the use of personal protective equipment, to emergency procedures that must be followed by all employees. This study employs library research or literature review. The result is by improving the effectiveness of the OHS system, it is expected that the number of workplace accidents will be reduced, as well as the creation of a safe and healthy working environment, providing benefits not only for workers, but also for the entire community that uses rail transportation service.